Enterovirus-like particles encapsidate RNA and exhibit decreased stability due to lack of maturation. - Louis Kuijpers; Evdokia-Anastasia Giannopoulou; Yuzhen Feng; Wouter van den Braak; Abbas Freydoonian; Ramon Ramlal; Hugo Meiring; Belén Solano; Wouter H Roos; Arjen J Jakobi; Leo A van der Pol; Nynke H Dekker (PLoS Pathogens)
To counteract hand, foot, and mouth disease-causing viruses such as enterovirus A71 and coxsackievirus A6, virus-like particles (VLPs) have emerged as a leading contender for the development of a multivalent vaccine. However, VLPs have shown rapid conversion from a highly immunogenic state to a less immunogenic state and low particle integrity lifetimes compared to inactivated virus vaccines, thus raising concerns about their overall stability. Here, we produce VLPs to investigate capsid stability using cryogenic electron microscopy (cryo-EM), mass spectrometry (MS), biochemical assays, and atomic force microscopy (AFM). In contrast to prior studies and prevailing hypotheses, we show that insect-cell produced enterovirus VLPs include encapsidated RNA fragments with viral protein coding sequences. Our integrated approach reveals that CVA6 VLPs do not undergo viral maturation, in contrast to virions; that they can encapsidate RNA fragments, similarly to virions; and that despite the latter, they are more brittle than virions. Interestingly, this indicates that CVA6 VLP stability is more affected by lack of viral maturation than the presence of RNA. Our study highlights how the development of VLPs as vaccine candidates should encompass probing for unwanted (viral) RNA content and establishing control of their maturation to enhance stability.